Extensive remodeling of the extracellular matrix during aging contributes to age-dependent impairments of muscle stem cell functionality - Schüler, Svenja C (2021)
During aging, the regenerative capacity of skeletal muscle decreases due to intrinsic changes in muscle stem cells (MuSCs) and alterations in their niche. Here, we use quantitative mass spectrometry to characterize intrinsic changes in the MuSC proteome and remodeling of the MuSC niche during aging. We generate a network connecting age-affected ligands located in the niche and cell surface receptors on MuSCs. Thereby, we reveal signaling by integrins, Lrp1, Egfr, and Cd44 as the major cell communication axes perturbed through aging. We investigate the effect of Smoc2, a secreted protein that accumulates with aging, primarily originating from fibro-adipogenic progenitors. Increased levels of Smoc2 contribute to the aberrant Integrin beta-1 (Itgb1)/mitogen-activated protein kinase (MAPK) signaling observed during aging, thereby causing impaired MuSC functionality and muscle regeneration. By connecting changes in the proteome of MuSCs to alterations of their niche, our work will enable a better understanding of how MuSCs are affected during aging.